Components of the metabolic syndrome: abdominal obesity and arterial hypertension in the context of the risk of oncological pathology (Bangladesh Journal of Medical Science, 2024)
Introduction Metabolic syndrome (MS) is the most important risk factor for cancer, although the full relationship between MS and cancer remains far from resolved. A number of studies have been conducted that indicate a certain connection between hormonal and inflammatory changes in adipose tissue and cancer.Objectives The aim of the paper was to study was to investigate the incidence of cancer in patients with MS lasting more than 10 years, and the degree of dependence on its components: abdominal obesity (AO) and arterial hypertension (AH).Methods For comparison by the same parameters data from patients without MS were analyzed. The crosstabulation method was used to estimate the odds ratio (OR) of carcinogenesis and 95% confidence intervals (95% CI).Results It was found that in patients with a duration of MS of 13.5±2.41 years, the initiation of oncological diseases was observed in every fifth participant, while in the absence of MS in every fourteenth patient.Conclusion AO is associated with an increased risk of developing hypertension, and both of these conditions are associated with an increased risk of cancer of various localization. The greatest risk was found in MS with grade I obesity in combination with hypertension, as well as with the patient’s age.Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 407-417